Need for orthognathic surgery in cleft patients from Northern Finland - Mateusz Podleśny; Leena Ylikontiola; George K. Sándor; Ville Vuollo; Virpi Harila (Medical Journals Sweden, 2024)
Objective: Northern Finland has a unique distribution of clefts compared to the rest of Europe and Finland. This may reflect the need for orthognathic surgery among Northern Finland's patient pool. The aim of this study was to compare previously operated patients aged 18 years or older with cleft lip, cleft lip and alveolus, cleft lip and palate, cleft palate and to evaluate the need for orthognathic surgery in order to achieve a stable and functional occlusion.  Materials and methods: The study group consisted of all 18-years-old cleft patients treated in the Oulu Cleft Center. The total amount of patients was 110. The patients were compared retrospectively using patients' hospital records. The majority of patients did not have any cleft-associated syndrome. The need for maxillary or bimaxillary orthognathic or corrective-jaw surgery was evaluated by the Oulu Cleft Team. A descriptive and statistical analysis was used to determine the need for orthognathic surgery according to sex and cleft type. Results: There were nineteen patients of the total of 110 patients who met the criteria requiring corrective-jaw surgery (17,3%). In total 12 males (25,0%) and 7 females (11,3%) were evaluated for the need of orthognathic surgery. Sixteen of the 19 patients had palatal involvement of the cleft. Conclusions: The need for orthognathic surgery was greater in the cleft lip palate and cleft palate patient groups compared to cleft lip alveolus or cleft lip groups. This study also found that males from Northern Finland need surgery more often than females.